Analysis of sales trend and forecast for commercial vehicles in Bangladesh market - Zaman, Quazi Asif-Uz- (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2016.